Remote assessment of surgical site infection (SSI) using patient-taken wound images: Development and evaluation of a method for research and routine practice. Issue 1 (February 2023) - Macefield, Rhiannon C.; Blazeby, Jane M.; Reeves, Barnaby C.; King, Anni; Rees, Jonathan; Pullyblank, Anne; Avery, Kerry
Abstract: Background/aim: Clinical assessment of wounds for surgical site infection (SSI) after hospital discharge is challenging and resource intensive. Remote assessment using digital images may be feasible and expedite SSI diagnosis. Acceptable and accurate methods for this process are needed. This study developed and evaluated the feasibility, acceptability and usability of a method for patients to capture standardised wound images for remote wound assessment to detect SSI. Materials and methods: The work was conducted in two phases. Phase I involved: i) a review of literature to identify key components of photography relevant to taking wound images, ii) development of wound photography instructions for patients and a secure process for transmission of images using electronic survey software and iii) pre-testing of the photography instructions and processing method with a sample of 16 patients using cognitive interviews and observations. Phase II involved a prospective cohort study of 89 patients to evaluate the feasibility, acceptability and usability of the remote method following discharge from hospital after surgery. Quality of the images was assessed by three independent clinical reviewers. Results: Some 21 key components for photographing wounds were identified from 11 documents. Of these, 16 were relevant to include in instructions for patients to photograph their wounds. Pre-testing and subsequent iterations improved understanding and ease of use of the instructions and the process for transmitting images. Fifty-two of 89 (58.4%) patients testing the method remotely took an image of their wound(s) and 46/52 (88.5%) successfully transmitted images. When it was possible to ascertain a reason for not taking/transmitting images, this was primarily health problems (n = 7) or lack of time/poor engagement with the study (n = 4) rather than problems relating to technology/competency (n = 2) or practical issues relating to the wound itself (n = 2). Eighty-seven (85.3%) of the 102 images received were evaluated to be of high quality and sufficient to remotely assess SSI by at least two independent reviewers. Conclusion: A simple, standardised and acceptable method for patients to take and transmit wound images suitable for remote assessment of SSI has been developed and tested and is now available for use in routine clinical care and research. Highlights: Remote wound assessment using images is a feasible option for research studies and routine clinical care. A method for patients to take and transmit wound images suitable for remote SSI assessment has been developed and tested. Photography instructions for patients were demonstrably effective in producing high quality images to assess the wound. Photography instructions and process to transmit images are reproducible and ready for use in research and routine follow-up.